2015
DOI: 10.1086/682170
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiology Tracks Phylogeny and Meets Ecological Models in an Iberian Gecko

Abstract: Because fitness of ectotherms, including reptiles, is highly dependent on temperature and water availability, the study of ecophysiological traits, such as preferred temperature (T p) and water loss rates (WLRs), may provide mechanistic evidence on the restricting factors to the species ranges. The Moorish gecko, Tarentola mauritanica, is a species complex with a circum-Mediterranean distribution. In the Iberian Peninsula, two sister parapatric forms of the complex, known as the Iberian and the European clades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 73 publications
(75 reference statements)
2
22
3
Order By: Relevance
“…Our investigation of morphological variation across clades and populations of the Moorish gecko in the Iberian Peninsula indicated that individuals from the populations of clade CII were smaller in body size than those of CIII (Figure ), confirming the results obtained in a previous ecophysiological study (Rato & Carretero, ). Despite a general tendency for individuals from AR to exhibit smaller body sizes as compared to those from populations of CIII, the ones most influential in driving the smaller body size of CII were the individuals from Isla Grosa (MU), which were remarkably smaller than those of any other continental population, possibly pointing to insularity as a driving factor.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our investigation of morphological variation across clades and populations of the Moorish gecko in the Iberian Peninsula indicated that individuals from the populations of clade CII were smaller in body size than those of CIII (Figure ), confirming the results obtained in a previous ecophysiological study (Rato & Carretero, ). Despite a general tendency for individuals from AR to exhibit smaller body sizes as compared to those from populations of CIII, the ones most influential in driving the smaller body size of CII were the individuals from Isla Grosa (MU), which were remarkably smaller than those of any other continental population, possibly pointing to insularity as a driving factor.…”
Section: Discussionsupporting
confidence: 89%
“…Diversification of the different lineages occurred during the Miocene and Pleistocene, associated with both divergence and conservatism of the macroclimatic niche related to temperature and precipitation (Rato et al., ). These results have been corroborated through ecophysiological studies in the two lineages distributed across the Iberian Peninsula (Clades II and III), which exhibit significantly distinct water loss patterns, supporting the hypothesis that this physiological trait is possibly related to the cladogenesis of T. mauritanica (Rato & Carretero, ). Furthermore, this same study detected that populations from Clade III exhibited greater variability concerning water loss values evidencing its ecophysiological flexibility, which has been suggested to enhance its invasive success across Europe.…”
Section: Introductionsupporting
confidence: 66%
“…the Gibraltar Strait), such niche shifts may have played a substantial role in the speciation processes of this group, as well as allowing it to occupy more northerly regions in Europe that would have been previously unavailable. Indeed, a recent ecophysiological study comparing multiple Iberian populations belonging to these two clades [ 76 ] reports clear differences in water loss rates. Overall, the European lineage displayed a trend for higher water loss when compared to the Iberian lineage.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of correspondence between ecophysiological traits and local climatic conditions, support the existence of a phylogenetic signal rather than local adaptation. These results suggest that divergent evolutionary responses to the environment in both lineages, mainly acting on water ecology, may account for the differences in their range expansion [ 76 ]. These findings reinforce the evidence that humidity-related conditions led to the divergence between these two clades, at least in the Iberian Peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…Although reptilian hydric ecophysiology is less studied, evaporative water loss (EWL) rates are known to differ between species from xeric and humid habitats ( Mautz , 1982b ; Eynan & Dmi’el , 1993 ; Carneiro et al , 2015 ; Rato & Carretero , 2015 ) and between phylogenetically distant species in the same locality ( Garcí a-Muñoz & Carretero , 2013 ; Osojnik et al , 2013 ). This makes EWL potentially informative on the hydric constraints of a species’ fundamental niche, particularly under restricted water availability ( Bowker , 1993 ).…”
Section: Methodsmentioning
confidence: 99%